Performance of Holstein cows fed wet corn gluten feed or soyhull-steep liquor pellets during early lactation - E.E. Ferdinand; Evan C. Titgemeyer; A.F. Park; J.M. DeFrain (Kansas Agricultural Experiment Station Research Reports, 2001)
Wet corn gluten feed and soyhull-steep liquor pellets tended to increase dry matter intake and milk yield. Combining condensed corn steep liquor with raw soybean hulls provides a convenient source of digestible fiber and rumen degradable protein.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Wet corn gluten feed; Soyhulls; Corn steep liquor